Ce que l’itinéraire nous dit du voyage. Listes d’itinéraire, voyage et imaginaire spatial au Soudan central au XIXe siècle - Camille Lefebvre (Afriques)
The European explorers who traveled in the central Sudan during the first half of the 19th century concentrated on gathering the geographical information necessary for drawing maps once they would return to Europe. Their method involved a daily, systematic account of the trips made by the companions and informants whom they met on the road or at places where they stopped over. Some of these lists of itineraries have survived and invite us to try to describe the scientific practices and geographical imagery on which they were based. By comparing them with linguistic data collected during the 19th century, we can place these itineraries in the context of traveling at the time in the central Sudan. This comparison enables us to propose a realistic account of the processes involved in these meetings and to give meaning to these hybrid reflections of the geographical and spatial conceptions then current in the central Sudan.